Multiple-Set Split Feasibility Problems for Asymptotically Strict Pseudocontractions - Shih-Sen Chang; Yeol Je Cho; J. K. Kim; W. B. Zhang; L. Yang (Abstract and Applied Analysis)
In this paper, we introduce an iterative method for solving the multiple-set split feasibility problems for asymptotically strict pseudocontractions in infinite-dimensional Hilbert spaces, and, by using the proposed iterative method, we improve and extend some recent results given by some authors.